Controlled Comparative Study of Post-operative Analgesic E?ect of Pre-emptive use of Pregabalin & Ketorolac in Patients Undergoing Single Level Decompressive Lumbar Laminectomy - Ankitkumar K Chauhan; Mona Bana; Rajeev Lochan Tiwari; Guriqbal Singh; Ishraq Khan (Academia Anesthesiologica International, 2021)
Background: Pre-emptive analgesia helps to reduce the physiological consequences of nociceptive transmission. Pregabalin has anti-convulsant, anti-hyperalgesic, and anxiolytic properties and Ketorolac is a nonsteroidal anti-inflammatory drug (NSAID) with potent analgesic effects and a relatively low incidence of side effects. The aim is to assess and compare post-operative analgesic effect of pre-emptive use of Pregabalin & Ketorolac in patients undergoing single level decompressive lumbar laminectomy. Subjects and Methods : It is randomised, prospective, double blinded study in which 75 patients of ASA physical status grade I and II scheduled for single level elective decompressive lumbar laminectomy (L2-3, L3-4, or L4-5) were enrolled in the study. They were then randomly divided into three groups of 25 each, group C (control), P (pregabalin) and K (Ketorolac) by chit-in box method.Patients in group C, P and K receivedplacebo drug, 150 mg pregabalin tablet and 10 mg ketorolac tablet respectively one hour before surgery with a sip of water. The patients werefollowed up to 24hr in post-operative period for pain relief and pain scoring was done by Numerical rating scale. Results: NRS was statistically insignificant at 1, 4, 12 & 24 hr. Rescue analgesic consumption at 1hr, 4hr, 12hr and 24hr was statistically insignificant.12%, 4% and 4% patients experienced drowsiness in group C, P and K respectively.32%,12% and 16 % patients experienced nausea and vomiting in group C, P and K respectively. Significantly higher mean systolic blood pressure is observed in group C at 1hr, 4hr and 12hr when compared to group P and group K. Significantly higher mean diastolic blood pressure is observed in group C at 1hr when compared to group P and group K. Conclusion: It was found that Pregabalin and Ketorolac do not decrease post-operative analgesic consumption when compared to control. There is no difference in adverse effect profile between Pregabalin and Ketorolac.